PTH-045 Multimodal endoscopic evaluation guides treatment decisions for early rectal cancers and complex rectal neoplasms. (17th June 2017) - Emmanuel, A; Gulati, S; Burt, M; Hayee, B; Haji, A
Abstract : Introduction: There is wide variation in the treatment of early rectal cancers and complex rectal neoplasms. With increasing emphasis on minimally invasive techniques and organ preservation, we aimed to evaluate the utility of a standardised, structured and rational assessment of rectal tumours to inform decision making for patients referred to a tertiary unit specialising in early rectal cancer. Method: Since 2012, our unit has employed a standard approach to the assessment of rectal lesions which includes multimodal endoscopic assessment of all lesions using white light, magnification chromoendoscopy and colonoscopic high frequency miniprobe ultrasound to inform treatment decisions. Patients can then be allowed a fully informed decision regarding treatment options, which include advanced endoscopic resection, minimally invasive transanal endoscopic microsurgery (TEMS) or laparoscopic segmental oncological resection, all of which are offered by our unit. Results: 191 patients (mean age 71 years) with rectal tumours were referred to our unit for an assessment regarding suitability for local resection. Multimodal endoscopic evaluation assessed 128 lesions as benign and 63 as malignant. 125 lesions with a mean size of 70.9 mm were treated with endoscopic resection: 108 adenomas, 9 adenocarcinomas and 5 neurendocrine tumours. 92% were performed without general anaesthesia and 78% as day cases. There were 2 small perforations treated endoscopically with clips with no adverse sequelae. The recurrence rate was 10%, all managed endoscopically. At last surveillance 97% of patients were free from recurrence. None required a major resection. 37 patients underwent TEMS as curative treatment or for patients unfit for, or refusing major resection. Only 3 patients with benign neoplasms had TEMS. The few remaining patients were either directed to major surgical resection, palliative options or declined treatment. Conclusion: A standardised rational approach employing multimodal endoscopic evaluation for assessing complex rectal neoplasms results in high rates of safe, effective organ preserving treatment with almost no patients with benign disease subjected to a surgical procedure. Disclosure of Interest: None Declared